Informed consent in translational/clinical research. Ethical issues according to international guidelines (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
In translational research, the emphasis on advancements in scientific knowledge could prevail over the protection and the best interest of those who participate in the research; in particular, the duty of safety for human subjects could become far more challenging when moving from preclinical research to first-in-human trials, because of uncertainty, as preclinical research can fail to predict the risks for humans, and of risk, which could result in a greater than minimal risk, because of the acceleration of research in the shift from bench to bedside. The article discusses from an ethical point of view specific issues which informed consent in translational research should take into account.
Keywords: Translational/clinical research; ethics; informed consent; safety; risk